HUBUNGAN ANTARA KECERDASAN INTERPERSONAL DENGAN PERILAKU MORAL ANAK USIA 5-6 TAHUN DI RAUDHATUL ATHFAL KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Rita Aryanti; Daviq Chairilsyah; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low moral behavior of children. Moral behavior has an important role in determining a person's behavior. Good moral behavior will have a positive influence on children's interpersonal intelligence. This study aims to determine the relationship between interpersonal intelligence with the moral behavior of children aged 5-6 years at Raudhatul Athfal Subdistrict inuman Kuantan Singingi District. This research is a quantitative research with a type of correlation research. Sampling technique used in this study is saturated samples with a sample of 69 people. Data collection techniques used are observation sheets. Data analysis technique uses Pearson Product Moment correlation technique. Based on the results of the hypothesis test is known from the correlation coefficient value of rxy = 0.695 greater than rtable = 0.236 (0.695> 0.236) with a significance level of 0.000 <0.05. Thus it can be concluded that there is a relationship between interpersonal intelligence and moral behavior. The level of the relationship is included in the strong category with the determinant coefficient value produced is equal to 48.3%, it can be seen that interpersonal intelligence contributes 48.3% to moral behavior.Keywords: Moral Behavior, Interpersonal Intelligence